PENGARUH MEDIA POP UP BOOK TERHADAP PEMAHAMAN SISWA PADA MATERI PERUBAHAN WUJUD BENDA KELAS IV SDN INPRES I RENDA - Nurhairunisah; Nurjumiati; Hendrawansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low level of students’ understanding in science learning at elementary schools, which is still dominated by lecture methods and the lack of attractive learning media. This study aimed to determine the effect of using Pop Up Book media on the understanding of fourth-grade students at SDN Inpres 1 Renda regarding the material of changes in the states of matter. The research used a quantitative approach with a Quasi Experimental Design through a One Group Pretest–Posttest Design. The research subjects consisted of 16 students. Data collection techniques were conducted through pretests and posttests, while data analysis used descriptive statistics, Shapiro-Wilk normality tests, and the Wilcoxon Signed Rank Test. The results showed that the average student score changed from 53.3 in the pretest to 77.4 in the posttest. In addition, the standard deviation decreased from 18.4 to 6.50, indicating that students’ understanding became more evenly distributed. The results of the Wilcoxon Signed Rank Test showed a significance value of p < 0.001, so H₀ was rejected and H₁ was accepted. Thus, the use of Pop Up Book media had a positive effect on students’ understanding of the material on changes in the states of matter. Pop Up Book media helped students understand concepts more concretely, attractively, and contextually so that students became more active and easier to understand the learning material.